Case Report: Novel TRPM6 Mutations Cause Hereditary Hypomagnesemia With Secondary Hypocalcemia in a Chinese Family and a Literature Review - Han, Yiran; Zhao, Yajuan; Wang, Hua; Huo, Liang (Frontiers in Pediatrics, 2022)
Background: Hereditary hypomagnesemia with secondary hypocalcemia (HSH) is a rare autosomal recessive disease due to biallelic TRPM6 mutations. Although the reports of HSH caused by TRPM6 mutations are not very rare, the age of onset in previously reported HSH cases were less than 1 year. Methods: We collected and analyzed the clinical data of twin brothers with onset age over 1 year old and performed whole exome sequencing in the patients and their parents. Confirmed by Sanger sequencing, missense mutation was analyzed in silico. We also searched Pubmed, and extracted clinical data from case reports and case series with full text in English, reporting original data of patients with TRPM6 mutations. Results: The twin patients had canonical HSH phenotype with compound novel TRPM6 mutations, p.T87K and c.705dupT, inherited from their father and mother, respectively. T87 is a highly conserved site and T87K is predicted to cause hydrogen bond disruption. We identified 26 articles published between May 28, 2002 to December 31, 2021 which reported a total of 88 patients with TRPM6 mutation. We found that the most common clinical phenotypes were hypomagnesemia, hypocalcemia, and convulsions. However, the age of onset in HSH patients almost always occurred under 12 months old, the twin patients of our study were 18 and 26 months old at onset. Conclusion: We identified two novel TRPM6 mutations in a Chinses family with HSH, and showed that the age of onset with c.704c-c.705(exon7)insT and c.260(exon4)C>A mutation in TRPM6 was much later than other mutations and would be much less serious.